Research on the seasonal driving mechanisms of benthic macroinvertebrate communities in streams - Feng, Yiyang; Yang, Mengyu; Chen, Hao; Tang, Fulin; Liu, Xin; Shi, Jialiang; Yang, Haijun (Frontiers in Ecology and Evolution, 2025)
In this study, the community structure and diversity of macroinvertebrate benthic animals in the 18 streams, Cangshan, Dali City, Yunnan Province, were investigated in detail. The main water environment factors driving the changes in these communities were analyzed, and the effects of the wet and dry seasons were explored. There were significant differences in the characteristics of the water environment and the community structure of benthic animals between the wet and dry seasons. In particular, the precipitation, water flow, and water temperature increased in the wet season, and the species diversity and functional diversity of benthic animals were significantly greater than those in the dry season. Through the analysis of the linear mixed effect model, in the wet season, the rainfall increases greatly, leading to the acceleration of the flow velocity and the increase in turbidity; rich nutrients and suspended particles enter the water, and a relatively high water temperature provides a relatively suitable habitat. The combined effects of these factors improve the species diversity and functional diversity of benthic animals. Moreover, the wet season coincides with the agricultural farming period in the area, and the increase in organic matter and nutrients in agricultural runoff also provides food for the reproduction of some benthic animals, leading to an increase in their diversity. These results suggest that the combined effects of such significant seasonal changes and human activities (agricultural development) need to be considered when protecting and managing aquatic ecosystems in regions with distinct wet and dry seasons. This study provides a key basis for the scientific formulation of water resource management policies, which not only helps maintain the health and stability of the ecosystem of the 18 streams in Cangshan but also provides a valuable reference for the seasonal protection and management of similar water ecosystems around the world.